Lipid biomarker patterns of authigenic carbonates reveal fluid composition and seepage intensity at Haima cold seeps, South China Sea. (December 2018) - Guan, Hongxiang; Birgel, Daniel; Peckmann, Jörn; Liang, Qianyong; Feng, Dong; Yang, Shengxiong; Liang, Jinqiang; Tao, Jun; Wu, Nengyou; Chen, Duofu
Highlights: Lipid biomarker patterns of active Haima seep carbonates were studied. UCM in seep carbonate reflects the presence of crude oil at Haima seeps. The predominant consortia in carbonates from both sites were ANME-1/DSS. Methane seepage was at least intermittently more intense at site ROV2 than at ROV1. Abstract: Authigenic carbonates retrieved from sites ROV1 and ROV2 of the Haima hydrocarbon seeps of the South China Sea at approximately 1390 m water depth were studied using lipid biomarker analyses. Abundant molecular fossils of anaerobic methane oxidizing archaea (ANME) and sulfate-reducing bacteria (SRB) with strong 13 C-depletions (δ 13 C values as low as −126‰), in combination with low δ 13 Ccarbonate values (−42.7‰ to −36.8‰), provide evidence that anaerobic oxidation of methane (AOM) was the major process driving the precipitation of the studied seep carbonates. The extremely low δ 13 C values of archaeal biomarkers confirm that biogenic methane was the main carbon source, but the seepage of accessory crude oil is also suggested by the presence of unresolved complex mixtures in the hydrocarbon fractions. A suite of 13 C-depleted biomarkers indicate the predominance of ANME-1/ DSS consortia at both sites, which indicates that the studied carbonates formed during low to medium methane flux. Somewhat higher contents of archaeal biomarkers and their stronger 13 C-depletion at site ROV2 probably reflect at least temporarily higher seepage intensities than at site ROV1. Abundant bacterial dialkyl glycerol diethers (DAGEs), revealing a large offset of their δ 13 C values compared to SRB-derived terminally branched fatty acids, were possibly produced by distinct SRB species other than members of the DSS cluster. The encountered hopanoids are attributed to aerobic methanotrophic bacteria based on their moderate 13 C-depletion. The application of molecular fossils in combination with their compound-specific isotope signatures is an efficient tool to reconstruct the composition of seepage fluids and seepage intensities.